The status of English modals prior to their recategorization as T and the trigger for their recategorization. - Castillo-Orihuela, Concepción (ICI Publishers Panel, 2022)
This is an account of English modals that invokes their exceptional morpho-syntactic tense properties as original preterite-present verbs in order to explain their becoming T elements. Within the framework of minimalist theory, I argue that modal verbs in OE and ME (up to approx. 1470) have an exceptional syntactic status that con- sists in that they merge directly under v, whereas strong verbs merge as a stem-by-default prior to v, and weak verbs merge as a root with a vowel-by-default also prior to v. Modals necessarily differ from both strong verbs and weak verbs in their τ–licensing, whereas they share with the latter (with both strong verbs and weak verbs) φ–licensing. A specific Probe of T is in charge of the latter for all verbs in the language. Modals pass on to merge directly under T when v ceases to be a locus of interpretable τ–features. A symptom that v loses such a capacity is the loss of the Pret.1/Pret.2 ablaut distinction.
Keywords: Verbos modales; Inglés - Gramática histórica; Minimalismo (Lingüística); Inglés - Verbo; OE modals; Strong verbs/weak verbs/preterite-presents; T-licensing; Phi-licensing; Inherent v-status; Recategorization as T by Late ME